Systematic position of Ascopus Marshall, Oreosecus Marshall, Perarogula Hoffmann and Rhadinocopes Hustache (Coleoptera: Curculionidae: Entiminae) with description of a new species of Ascopus from Guinea - Borovec, Roman; Perrin, Hélène (Zootaxa, 2019)
Type material of the described species of Ascopus Marshall, 1951, Oreosecus Marshall, 1950, Perarogula Hoffmann, 1963 and Rhadinocopes Hustache, 1931 was examined and their taxonomic status is discussed. Oreosecus Marshall, 1950 and Rhadinocopes Hustache, 1931 are proposed as junior synonyms of Tapinomorphus Hartmann, 1904, Perarogula Hoffmann, 1963 is proposed as a junior synonym of Ascopus Marshall, 1951. Rhadinocopes curvipes Hustache, 1931, R. echinatus Marshall, 1951 and Perarogula lamottei Hoffmann, 1963 are transferred as valid species to the genus Ascopus, Rhadinocopes alticola Hustache, 1939, R. orientalis Hustache, 1931 and Oreosecus porculus Marshall, 1950 are transferred as valid species to the genus Tapinomorphus. Lectotypes of Rhadinocopes orientalis Hustache, 1931 and Rhadinocopes alticola Hustache, 1939 are designated. Ascopus girardi sp. nov. from Guinea, Mt. Nimba, is described and compared with all other species of the genus. Male and female genitalia of Ascopus are described and illustrated for the first time. A key to Ascopus species is presented.